Good Corporate Governance: Firm Performance and Ownership Causality Test - Tri Gunarsih; Setiyono Setiyono; Fran Sayekti; Tamas Novak (Jurnal Keuangan dan Perbankan, 2018)
Ownership structure, among other things, is one mechanism in corporate governance. In this context, ownership has a monitoring function. Another corporate governance mechanism is the market for corporate control. If managers did not act in the best interest of shareholder, then firm performance will decrease. The changing in ownership will follow the decreasing of firm performance. This will raise an interesting question, whether ownership caused by firm performance or vice versa. The objectives of this study to test whether monitoring function or market for corporate control that was implemented as a corporate governance mechanism in Indonesia using causality model. A panel Granger-causality test base on Ganger (1969) applied to test the causality. Samples in this study were manufacture listed companies in Indonesia Stock Exchange during 2012-2016. Ownership concentration was proxy by the Herfindahl Index of Domestic Institution ownership. The firm performance indicators in this study were efficiency, measured by Operating cost to Sales ratio, and Sales to Asset ratio and Tobin’s Q. The results of the study showed that there was a bi-causality relationship between ownership concentration and both firm performance indicators. These suggested that the monitoring function and the market for corporate control were implemented as a corporate governance mechanism in Indonesia.    JEL Classification: G32, G34, G23DOI: https://doi.org/10.26905/jkdp.v22i4.2469